2019
DOI: 10.3389/fpsyg.2019.02023
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Dark Triad and Internet Adaptation Among Adolescents in China: Internet Use Preference as a Mediator

Abstract: This study aims to examine the relationship among the Dark Triad personality traits, Internet use preferences and Internet adaptation. In all, 1927 middle school students (aged 11–18) from Beijing and Kunming in China completed a self-reported questionnaire that measured the Dark Triad, Internet use preferences (information communication, recreation, information acquisition and online transaction) and Internet adaptation (positive/negative Internet adaptation). Correlations revealed that there were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The results of another study indicated that social zapping (i.e., the inclination to cancel or switch between social schedules at the last minute in favor of more valuable alternatives) was mainly predicted by Machiavellianism and narcissism [22]. It should also be noted that the DT of personality traits are not maladaptive but are the result of an individual's active adaptation to the environment [19]. Smartphones can be regarded as a technological tool that allows individuals to get access to modern services and applications.…”
Section: Dark Triad Of Personality and Problematic Smartphone Usementioning
confidence: 96%
See 1 more Smart Citation
“…The results of another study indicated that social zapping (i.e., the inclination to cancel or switch between social schedules at the last minute in favor of more valuable alternatives) was mainly predicted by Machiavellianism and narcissism [22]. It should also be noted that the DT of personality traits are not maladaptive but are the result of an individual's active adaptation to the environment [19]. Smartphones can be regarded as a technological tool that allows individuals to get access to modern services and applications.…”
Section: Dark Triad Of Personality and Problematic Smartphone Usementioning
confidence: 96%
“…The DT of personality affects a variety of behaviors in different domains, usually in a way that is somewhat deviant. Prior research has examined the association between the DT of personality and the problematic use of technologies [18] and other online addictive disorders related to PSU [19]. For example, the results of a recent study suggested that the DT of personality may play a causal role in higher PSU (with different traits having diverse effects among gender), and that attachment styles partially explained the association between dark traits and PSU [13].…”
Section: Dark Triad Of Personality and Problematic Smartphone Usementioning
confidence: 99%
“…Compared with Internet addiction, a more positive results of internet use is internet adaptation, which refers to an individual’s ability to effectively manage and balance online and real-world activities, academics, and social interactions in a digital environment ( 8 ). Specifically, internet adaptation involves how one negotiates the relationship between the online world and reality, whether internet usage behaviors conform to social norms, the impact on one’s academics and life, and the rationality of internet use ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their interpersonal difficulties, these individuals have the inclination to exploit their social contacts (Jonason & Schmitt, 2012;Moshagen et al, 2018Moshagen et al, , 2020. Therefore, individuals with salient Dark Triad traits actively seek gratification online, thus inducing their reliance on the Internet (Jin et al, 2019). Due to the associated impulsiveness, those with these salient dark traits are more likely to abuse substances to elicit gratification (Flexon et al, 2016;Stenason & Vernon, 2016), and they are susceptible to behavioral addictions, such as social network sites addiction (Chung et al, 2019;Lee, 2019).…”
Section: The Dark Triad Personalitymentioning
confidence: 99%